State Street at Congress Street, ca. 1885-90 - Unknown (Tufts Archival Research Center, 2005)
Elevated view east-southeast of (right to left) 39-67 State Street, located at the intersection of State and Congress Streets. The Tremont National Bank Building, located at 39-43 State Street at Congress Street, is included near the right side of the photograph. The columned-facade of the Boston Exchange Company, located at 49-57 State Street, is included in the center of the photograph. The facades of the buildings face north-northwest. Three men stand on the sidewalk in front of the Tremont National Bank Building. 5 5/8 x 8 1/4, 6 x 8 5/8 overall Photographs